The Correlation Between Students’ Self-Esteem and Their Writing Ability - Vilani, Selvia; Sugiarto, Dody (English Education Department, 2023)
This study was aimed to figure out the most dominant students’ self-esteem, whether there was any significant correlation between the students’ self-esteem and their writing ability and whether there were differences between students in their self-esteem. The participants of this study were tenth grade students in Payabenua subdistrict, Bangka Belitung province. The data of this study were collected by providing questionnaire sheets in the form of close ended questionnaire and writing test. Furthermore, the results were analyzed by using Pearson Product Moment to correlate both variables students’ self-esteem (X) and writing ability (Y). The result showed that the most dominant students’ self-esteem was the domain of self-esteem with the percentage of 55.38%. Since the correlation coefficient computation was 0.228, and the critical value in a table at significant level 0.05/5% was 0. 2441. Thus, rxy was lower than r-table. In brief, there was no significant correlation between students’ self-esteem and their writing ability. In addition, there was also no significance difference between male and female students’ self-esteem.